2020
DOI: 10.1080/0284186x.2020.1759822
|View full text |Cite
|
Sign up to set email alerts
|

Rate of locoregional recurrence among patients with oropharyngeal squamous cell carcinoma with known HPV status: a systematic review

Abstract: Background: We aimed to review systematically the literature on locoregional recurrence rates in patients with HPV-positive and-negative oropharyngeal squamous cell carcinoma (OPSCC). Methods: PubMed and Embase databases were systematically searched using key words such as human papillomavirus, oropharyngeal squamous cell carcinoma with local, regional, and locoregional recurrence. Results: Nine studies (2974 patients with known HPV-status, 59% HPV-positive) were included. Among the HPV-positive and-negative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…In some studies patients were stratified into highrisk volumetric subgroups [20,21,23,25,44,45]. The great majority of these studies (5 out of 6) focused on carcinomas of the pharynx (two studies [20,45] on hypopharyngeal SCC and three studies [21,23,25] on oropharyngeal SCC).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies patients were stratified into highrisk volumetric subgroups [20,21,23,25,44,45]. The great majority of these studies (5 out of 6) focused on carcinomas of the pharynx (two studies [20,45] on hypopharyngeal SCC and three studies [21,23,25] on oropharyngeal SCC).…”
Section: Resultsmentioning
confidence: 99%
“…Nodal volumetric analysis in patients with oropharyngeal, both HPV-positive and HPV-negative, and hypopharyngeal carcinomas appears to represent a challenging and promising field for research. Of particular note, in a quite recent systematic review [44], it was shown that the locoregional recurrence rates for HPV-negative (26%) patients are significantly higher (i.e., almost three times higher) as compared to HPV-positive (9%) OPSCC patients. This finding, in combination with the results of a multicentric study by Culie et al (2021) [45], wherein pri-mary surgical treatment in patients with p16-negative OP-SCC was found to be associated with improved overall survival (OS), disease-specific survival (DSS) and RFS, further supporting that patients with p16-negative OPSCC represent a group at high risk for recurrence, and metastatic nodal tumor volume could serve as an independent and decisive factor for risk stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 26% and 10% of patients with locally advanced HPV-negative and HPV-positive HNSCC, respectively, are affected with locoregional recurrences after treatment [4,5]. Radioresistance is one of the main reasons behind tumor relapse seen in these patients [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Around 60% of HNSCCs present with locally advanced but non-metastatic disease and are associated with poor survival outcomes [2]. The pattern of treatment failure is loco-regional; many patients go on to die from this disease without developing distant metastases [3][4][5]. Radical (chemo)radiotherapy ((C)RT) involving 6-7 weeks of daily RT with concurrent platinum-based chemotherapy is widely accepted as standard of care in locally advanced HNSCC.…”
Section: Introductionmentioning
confidence: 99%